Trade protectionism and international monetary order: Recalling the relevance of past experience - Juergen B. Donges (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1987)
After World War II, all industrial countries have reached a level of prosperity unprecedented in history; many developing countries and several socialist countries have experienced notable economic growth too. The post-war multilateral trading and monetary systems have been singled out by politicians, businessmen and academic economists as main institutional pillars for these achievements; they permitted positive net effects on resource allocation, economies of scale, international capital movements and the transfer of technology.
Keywords: 330; Protektionismus; Internationales Währungssystem